Perspektif Perdagangan Maritim di Selat Malaka Berdasarkan Data Baru Hasil Observasi di Situs Pulau Kompei - Stanov Purnawibowo (Balai Arkeologi Sumatera Utara, 2010)
AbstractThe presence of new data on the observation of archaeological sites on Kompei Island in 2010 could provide variety of data and reinforce the interpretation with respect to the tracking of maritime trade activity on the Kompei Island. Through the formal research, spatial and temporal to which inherent in archaeological data, the data of observation in 2010 combined with the data from various observations will provide another illustration in the searching of maritime trade activities in the East Coast of Northern Sumatera.